Peningkatan Kapasitas Bisnis dengan Vacuum Packs Silage pada Kelompok Tani Lestari - Widiyastuti, Tetty; Sunrowiyati, Siti; Puspitorini, Palupi; Widyasworo, Agustina; Winurdana, Alfan Setya; Sunandes, Aris (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service program aimed to enhance the business capacity of the Lestari Farmers Group in Tegalrejo Village, Selopuro District, Blitar Regency, through the implementation of vacuum-packed silage technology. The group, consisting of 36 ruminant livestock farmers, faced key challenges, including limited knowledge of grass-based feed management, suboptimal utilization of excess forage during the rainy season, and traditional business practices. The intervention methods included socialization, technical training on corn stover silage production, vacuum-packaging technology, business management mentoring, market development, and program evaluation for sustainability. The results demonstrated significant improvements: silage production capacity increased from zero to 1,000 kg/month within two months, feed loss was reduced by 30%, and silage quality improved with an optimal pH of 3–4. In terms of management, 100% of group members adopted basic bookkeeping and standardized operational procedures. Digitally enhanced marketing through social media and e-commerce expanded market reach compared to conventional methods, increasing silage pack sales revenue by Rp. 500,000. The program not only boosted income and production efficiency but also established a new value-added business unit specializing in packaged corn stover silage. This integrated model of appropriate technology adoption coupled with management training proved effective and can be replicated for similar livestock farmer groups.